A review on ZnO: Fundamental properties and applications. (2022) - Sharma, Dhirendra Kumar; Shukla, Sweta; Sharma, Kapil Kumar; Kumar, Vipin
Abstract: Among the semiconductor metal oxides, some semiconductor structures are identified for their unique and vast potential applications in optoelectronic, field effect transistors, solar cells, photoluminescence devices, and diluted magnetic semiconductors, etc. The interesting development in optoelectronic applications arises due to environmentally friendly short energy, laser diodes and white light producing technologies that work beyond room temperature. Out of this ZnO is an adaptable material for scientific study. The variation of ZnO properties by insertion of impurity/dopant has turn into a recent emerging matter. The phenomena of doping in ZnO i.e. ZnO as a host material will create by researchers; tailoring its optical, structural, electrical and magnetic properties through modifying its electronic structure. Due to doping results, there is enhancement in diverse applications like electronic, spintronic, optoelectronic, photocatalytic, antibacterial, etc. These improvements in different application areas are due to its direct band gap energy, luminescence, high electron mobility, and debatable room-temperature ferromagnetic conduct in diverse structures like single crystals, thin films, powders and nanostructure. This review extensively focused on the comprehensive cross-section of ZnO's luminescent, structural, optical, magnetic properties and various applications, with the key directions of development, serving as beginning, an orientation, and stimulation for upcoming research.